Corporate Events’ Effect on Stock Returns: Evidence from Athens Stock Exchange - Aristeidis Samitas; Dimitris Kenourgios; Ioannis Tsakalos (International Research Journal of Applied Finance, 2011)
This study examines firm’s stock returns’ behaviour, when they announce corporate events like management change, collaborations and stock repurchase. It examines how this change is portrayed in firms’ stock prices returns. The methodologies used are the methodology of event study analysis and bootstrap methodology. Companies selected belong to eight different sectors of Athens Stock Exchange with different Stock Exchange value in order to get a more general picture that does not only represent one sector which can be influenced individually from accidental factors. The sample constitutes forty firms listed in Athens Stock Exchange. Results indicate that corporate events’ impact is important and a key for enterprises to follow new challenges and create financial value. This paper provides evidence on the impact of corporate governance on stock returns in Greece. The implication is that corporate events create financial value.